Empowering Teachers with the Application of a Process Approach in Indonesian Language Learning in Surakarta City Junior High School - Ari Suryawati Secio Chaesar; Andayani; Suyitno; Arif Setyawan (Universitas Lancang Kuning, 2023)
The learning process during the Covid-19 pandemic presents a new paradigm, namely learning which was originally teacher-centered, shifting towards a students-centered learning paradigm by utilizing network media. Thus, it is necessary to coordinate cooperatively between teachers and students to create attractive, innovative, creative, and meaningful learning. However, in reality there are still obstacles faced but Indonesian language teachers, such as the not yet optimal application of the approach in the learning process in accordance with the latest curriculum and the absence of practical guidelines in activiting students in learning Indonesian during the pandemic and post-pandemic. Therefore, Community Service (PkM) activites aim to change the mindset of the Indonesian language teacher audience from teacher-centered learning to student-centered learning by applying a process approach, as well as improving the quality of student learning from learning about language to learning to use language. The method used in PkM is through the stages of problem identification and field studies, making books, training for teachers, practical training in the application of the process approach, as well as monitoring and evaluating the implementation of activities. The results of PkM activities can be concluded that partners understand and implement in practical exercises. Comments are based on PkM activities, namely that participants are enthusiastic about the material presented and hope that the training will continue to be developed by adding discussion topics and practice exercises to Indonesian language subject matter in Junior High Schools.